PEN and WASH : an artist's guide to combining ink and watercolour - Harrison, John (Ramsbury, Marlborough : THE CROWOOD PRESS, 2024)
"Pen and Wash is a practical guide to creating a picture that captures the discipline of pen, along with the subtlety of watercolour. With clear instruction and inspirational examples throughout, it explains the conventional approach of drawing and then adding wash, but also explores alternative ideas and styles. The author's passion for the technique is evident in his examples and enthusiastic text, making the book a superb guide to this beautiful medium. Advise on the correct equipment, techniques, the unpredictable nature of watercolours and Step by step demonstrations of pen and wash techniques"--
Includes bibliographical references and index
Keywords: Watercolor painting; Watercolor painting -- Technique; Pen drawing; Pen drawing -- Technique